Analisis Sintakmatik Permainan Simulasi Berlatar Isu-Isu Kontroversial Untuk Meningkatkan Keterampilan Menganalisis Informasi Pada Siswa SMA - Suryanto, Suryanto; Widodo, Agus; Salim, Nur (Universitas Nusantara PGRI Kediri, 2018)
The skills of analyzing information that often develop through social media and causing controversy are indispensable for young prospective students. Simulation games are thought to be effective for developing skills in analyzing information that are part of the formation of students' interpersonal skills, and are closely related to civic skills. Based on this, the issues that will be discussed in this paper are: how is the syntax of simulation games with controversial issues suitable for the development of the ability to analyze information on high school students ?. This paper is part of the preliminary study results for the purpose of simulation game development based on controversial public policy issues to instill constitutional democratic values ​​on high school students. Based on interviews with high school PPKn teachers, it is concluded that students need to have the skills to analyze information (hoax information) that often develop through social media lately. While simulated game syntax of controversial issues to improve the skills of analyzing hoax information are: (1) description of simulation game model, (2) assumption of model development, (3) game steps, (4) social system, (5) system (6) the principle of reaction, (7) the instructional impact, and (8) the impact of the companion.